Innovative Strategies of SMEs in Alignment with Community Needs - Sutrisno; Diawati, Prety; Muhamad, Lili Fadli; Permana, Riko Mersandro; Suparwata, Dewa Oka (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
SMEs play a crucial role in a country's economy, contributing significantly to GDP, job creation, and income distribution. However, SMEs often face significant challenges, particularly in competing with large corporations and adapting to changing consumer needs. This research focuses on the identification and analysis of innovative strategies that can help SMEs align themselves with community needs. The study adopts a qualitative literature review approach, gathering data from Google Scholar for the period 2018-2023. The results indicate that, in facing challenges and opportunities in the economic landscape, innovative strategies for Micro, Small, and Medium Enterprises (SMEs) become a fundamental foundation to ensure their relevance and sustainability. A profound understanding of societal needs, the implementation of technology, collaboration, and the enhancement of management skills are key elements in formulating an effective innovative strategy. Through these steps, SMEs can become agents of change, not only meeting consumer expectations but also contributing to sustainable economic growth.